ABUNDANCE AND DISTRIBUTION OF ANOPHELES MOSQUITO IN RELATION TO PHYSICOCHEMICAL PROPERTIES IN DELTA STATE, NIGERIA - Ojianwuna, C. C.; Enwemiwe, Victor; Ekeazu, C. N. (FUDMA JOURNAL OF SCIENCES, 2021)
In this study, the effect of physicochemical parameters as determinants for the abundance and distribution of Anopheles mosquitoes was examined. Physicochemical variables such as pH, temperature, DO, TDS, flow velocity, salinity and electrical conductivity were determined using standard procedures. Three communities in Ukwani LGA, Delta State were mapped out and sampled. Immature stages of Anopheles mosquitoes were collected from potential breeding sites using 350 ml dip ladles and scooping spoon. The physicochemical parameters showed that air, and water temperature, pH, and dissolved oxygen were higher in Umutu compared to the other sampled communities (Obiaruku and Umukwata). Salinity, conductivity, total dissolved solids and flow velocity were higher in Obiaruku and Umukwata compared to Umutu. Various levels of significance (p
Keywords: Abundance, Anopheles mosquitoes, Delta State, Distribution, Physicochemical parameters